PELAKSANAAN PERATURAN DESA MEKONG NOMOR 02 TAHUN 2017 TENTANG PEMBENTUKAN BADAN USAHA MILIK DESA LESTARI DI DESA MEKONG KECAMATAN TEBING TINGGI BARAT KEBUPATEN KEPULAUAN MERANTI TAHUN 2019 - Rian Kurnia; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The establishment of village-owned enterprises is based on Law No. 6 of 2014 concerning villages, as well as Government Regulation No. 43 of 2014 concerning Implementing Regulations of Law No. 6 of 2014 concerning Villages. The Meranti Islands Regency Government mandates that every Village Government establish a Village-Owned Business Entity which is listed in Regent Regulation No. 33 of 2017 concerning Implementation Guidelines for Village/Kelurahan BUM. Mekong Village Regulation No. 02 of 2017 concerning the Establishment of Sustainable BUMDes (BUM Desa) Mekong Village has not been fully implemented in accordance with the mandate, such as multiple directors, establishment of business units not through village consultations, BUMDes Lestari has not been able to maximize village potential and lack of human resources in management BUMDes. The formulation of this research is "How is the implementation of Mekong Village Regulation Number 02 of 2017 concerning the Establishment of Sustainable Village BUM (BUM Desa) Mekong Village in Mekong Village, Tebing Tinggi Barat District, Meranti Islands Regency in 2019?" The purpose of this study is to analyze and describe the implementation of Mekong Village Regulation No. 02 of 2017 concerning the Establishment of BUM Desa Lestari Mekong Village in Mekong Village, Tebing Tinggi Barat District, Meranti Islands Regency in 2019. This research is a type of descriptive research. Data collection techniques in this study used interviews, field observations and documentation. Data analysis techniques using data reduction methods, data presentation and drawing conclusions. The findings that can be concluded are that the implementation of the Mekong Village Regulation No. 2/2017 concerning the Establishment of Sustainable BUMDes in Mekong Village in Mekong Village is less than optimal, this is based on the results of research findings in the field, namely: 1) Content of Policy, the dominant actor in proposing BUMDes business units is the village head should be carried out by deliberation, consensus, and transparency. Then the benefits of implementing the village regulation have not been felt to the fullest, have not been able to increase sales results in PADes significantly, there is no clear target from BUMDes related to sales and strategies, there are still multiple positions, and the HR management of BUMDes is not adequate, and the selection of BUMDes directors is not appropriate. procedure. 2) Context of Policy, the strategy carried out by the BUMDes management has not shown significant results since the sustainable BUMDes was established, and the response from the BUMDdes program implementers is very good, but the level of discipline of the BUMDes management is classified as lacking discipline and has not carried out its duties and functions optimally. Keywords: Policy Implementation, Policy Content, Implementation Environment, Sustainable BUMDes.